A Critical Review of the Sustainability of South Africa's Health System, User’s Satisfaction and Key Performance Scores - Shenaaz GANI (International Journal of Environmental, Sustainability, and Social Science, 2023)
The South African Government has made accessibility and equity the primary focus of its health policy objectives since 1994. However, the extent to which these policies achieve their aims of lessening inequality is not synthetically documented. This study critically reviews and synthesises the literature on the nature of the South African health system, user’s satisfaction and key performance scores. The study conducted a content analysis of several research papers and policy papers in the South African health sector. The review showed that the current health system is dualistic, indicating that the public health system is not living up to the National Core Scores and that this has impacted negatively on the level of satisfaction of households. The evidence demonstrated ongoing discrepancies in access to and use of health services, notwithstanding legislative initiatives. Moreover, the review showed that user’s perceptions of the quality of public healthcare services are deteriorating in South Africa. There is evidence of treatment delays, long waiting times, acute shortages of doctors, specialists and nurses, a lack of appropriate medication and poor health services delivery. The evidence provided about the South African health system can contribute to global policy discussions about health equity on the use of health services by households from different socioeconomic backgrounds and how policies can increase access to quality health care for low-income households.